Potential Review Assessment as a Competency Evaluation Tool for the Group Leader Repair and Maintenance Position - Vivany, Farah Fauziah; Adiati, Rosatyani Puspita (Universitas Syiah Kuala, 2025)
This study aims to evaluate the suitability between individual competencies and competencies required for the position of Group Leader Repair Maintenance at PT X through the Potential Review Assessment approach. The method used refers to the potential assessment model which consists of six main stages, namely job modeling design, preparation of assessment protocols, implementation of the assessment process, integration and interpretation of results, preparation of reports, and evaluation of assessment implementation. The results showed that of the seven competencies assessed, there were two core criteria and one supporting criterion that were below the grey area, indicating that there was a competency gap between the subject and the need for the position. Based on the recommendation category, the subject is not recommended to occupy the position. In general, the assessment process has been carried out according to procedures and meets ethical aspects, such as the protection of personal data and the provision of informed consent. However, limitations in determining predictors by the bureau, lack of information from the company's internal Subject Matter Expert (SME), and in-depth interviews are obstacles in obtaining fully comprehensive assessment results. These findings affirm the importance of continuous evaluation of the implementation of assessments as an effort to improve the accuracy and relevance of data in the context of work competency assessment in organizations.